2020
DOI: 10.1016/j.eurpolymj.2020.110019
|View full text |Cite
|
Sign up to set email alerts
|

Metalated porphyrins as versatile visible light and NIR photoinitiators of polymerization

Abstract: A series of metalated porphyrins has been prepared and used as visible light photoinitiators of polymerization activable under low light intensity. Among the six metalated porphyrins examined in this work, five of them have never been reported in the literature and specifically designed to exhibit a good solubility in monomers. Three of the proposed structures were efficient @405nm but remarkably, despites their weak absorptions at 785 nm, efficient Near Infrared (NIR) polymerization profiles could also be obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…To our knowledge, this is the first use of a porphyrinoid-based three-component system for red-light FRP initiation without adding a thermal initiator. 23,38 While chlorophyll b and chlorophyllin have been reported as slow initiating photoinitiators under red light, 14 Pyro and Zn-Pyro allow conversions of up to 60% to be reached under LED@625 nm in this study. Surprisingly, although Pyro/MDEA was the only two-component systems able to initiate polymerization under air according to the formation of aminoalkyl radicals (see EPR results), Pyro/Iod/MDEA could not.…”
Section: Papermentioning
confidence: 60%
See 1 more Smart Citation
“…To our knowledge, this is the first use of a porphyrinoid-based three-component system for red-light FRP initiation without adding a thermal initiator. 23,38 While chlorophyll b and chlorophyllin have been reported as slow initiating photoinitiators under red light, 14 Pyro and Zn-Pyro allow conversions of up to 60% to be reached under LED@625 nm in this study. Surprisingly, although Pyro/MDEA was the only two-component systems able to initiate polymerization under air according to the formation of aminoalkyl radicals (see EPR results), Pyro/Iod/MDEA could not.…”
Section: Papermentioning
confidence: 60%
“…Some examples of FRP under NIR were reported with porphyrin initiators, but using four-component systems to combine photothermal and photochemical initiation. 23,38 Although synthetic products can show impressive photochemical properties, porphyrin derivatives also exist in nature, and take part in vital biological processes: chlorophyll a, which is the mainstay of photosynthesis; haemoglobin, which is the oxygen carrier in the blood; or the corrin structure at the base of vitamin B12. 39 Several natural dyes have already been studied and found to promote photopolymerization under visible light, [40][41][42][43] but they generally do not absorb in the red light range, contrary to free base porphyrins that possess absorption bands, namely Q bands, up to 650 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Considering that the development of visible light photoinitiating systems activable under low light intensity and in the visible range is extremely recent, this research is still in a prospective phase, at the search of innovative structures that could act as visible light photoinitiators of polymerization. In the course of the different investigations, a wide range of structures have been examined and naphthalimides, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] porphyrins, [42,43] chromones and flavones, [44][45][46][47][48] acridones, [49,50] carbazoles, [51][52][53][54][55][56][57][58] benzophenones, [59][60][61][62][63][64] pyrenes, [65][66][67][68][69][70] diketopyrrolopyrroles, [71]...…”
Section: Temporal Control High Polymerization Speed Spatial Controlmentioning
confidence: 99%
“…With long wavelengths and good tissue penetration, the near‐infrared (NIR) light has been utilized to stimulate controlled/living polymerization, either by incorporating upconversion nanoparticles (UCNPs) [ 27–33 ] or using photocatalysts with NIR light presence. [ 34–39 ] The use of UCNPs in photopolymerization is creative, but it also inevitably increases the complexity of the system. Boyer et al.…”
Section: Introductionmentioning
confidence: 99%
“…With long wavelengths and good tissue penetration, the near-infrared (NIR) light has been utilized to stimulate controlled/living polymerization, either by incorporating upconversion nanoparticles (UCNPs) [27][28][29][30][31][32][33] or using photocatalysts with NIR light presence. [34][35][36][37][38][39] The use of UCNPs in photopolymerization is creative, but it also inevitably increases the complexity of the system. Boyer et al reported the use of phthalocyanine compounds, [40,41] and bacteriochlorophyll 𝛼 [42] as a photoinitiation system for RAFT polymerization under NIR wavelengths.…”
Section: Introductionmentioning
confidence: 99%